Pengaruh Likuiditas, Leverage, Posisi Kas, dan Ukuran Perusahaan Terhadap Kebijakan Dividen - Sonya Enda Natasha S. Pandia; Evi Juita Wailan’An (Universitas Methodist Indonesia, 2024)
This research aims to determine and analyze the effect of liquidity, leverage, cash position and company size on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population obtained in this study amounted to 271 companies. The method used in sampling in this research used a purposive sampling method and obtained as many as 32 companies as samples. The data used in this study was taken from the financial reports of manufacturing companies for the 2017-2021 period. The method used to test the data in this study is multiple linear regression analysis. The results of this research show that simultaneously liquidity, leverage, cash position, and company size influence dividend policy. Partially, in this study the liquidity variable effect on dividend policy. While leverage,and company size have no effect on dividend policy.